1992
DOI: 10.3168/jds.s0022-0302(92)78041-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cation-Anion Balance and Cation Source Effects on Production and Acid-Base Status of Heat-Stressed Cows

Abstract: Two 4 x 4 replicated Latin square studies, each containing 8 lactating Holstein cows, were conducted simultaneously in south Georgia during the summer. The effects of dietary cation source (Na or K) and increasing dietary cation-anion balance (milliequivalents of Na + K - Cl per kilogram of feed DM) within cation source (control = 120.4 meq/kg of feed DM; Na source = 219.7, 347.8, 464.1 meq/kg of feed DM; K source = 231.2, 352.6, 456.0 meq/kg of feed DM) were determined on performance and acid-base chemistry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
71
1
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 17 publications
41
71
1
6
Order By: Relevance
“…Ruminant kidneys are highly sensitive to blood acid base status and increase the excretion of Ca during acidosis, independent of the hormonal action usually associated with Ca metabolism (Stacy and Wilson, 1970). These results are in concordance with West et al (1992) who observed an increased urinary Ca: creatinine (0.30 versus 0.09) excretion with increased (120 versus 465 mEq/kg) level of DCAD. Alteration in fecal Ca excretion might be attributed to dietary concentration of this mineral.…”
Section: Calcium Balancesupporting
confidence: 73%
See 1 more Smart Citation
“…Ruminant kidneys are highly sensitive to blood acid base status and increase the excretion of Ca during acidosis, independent of the hormonal action usually associated with Ca metabolism (Stacy and Wilson, 1970). These results are in concordance with West et al (1992) who observed an increased urinary Ca: creatinine (0.30 versus 0.09) excretion with increased (120 versus 465 mEq/kg) level of DCAD. Alteration in fecal Ca excretion might be attributed to dietary concentration of this mineral.…”
Section: Calcium Balancesupporting
confidence: 73%
“…Tucker et al (1988) also reported decreased feed intake in cows fed CaCl 2 . Decreased DMI with reduced DCAD level of diet had also been reported by West et al (1991West et al ( , 1992.…”
Section: Nutrient Intake and Digestibilitymentioning
confidence: 57%
“…In the present study CaCl 2 (1.75%) was used to achieve the required (− 110) DCAD level. Decreased DMI with reduced DCAD level of diet has also been reported by other workers (West et al, 1991(West et al, , 1992Spanghero, 2004).…”
Section: Nutrients Intake and Their Digestibilitiessupporting
confidence: 58%
“…O teor de gordura do leite não se alterou em função do BCAD (P>0,05). Este resultado concorda com aquele observado por WEST et al (1992), os quais, estudando diferentes níveis de BCAD e duas fontes de cátion (Na e K) para vacas holandesas em lactação sob estresse térmico, não verificaram alterações nas concentrações de gordura do leite em função dos diferentes níveis de BCAD. Entretanto, houve aumento da gordura do leite para a fonte de Na quando comparada com a fonte de K, para um mesmo valor de BCAD.…”
Section: Resultsunclassified